Konflik Agragria di Tulungagung dan Penyelesaiannya Secara Hukum - Ade Aslama; Elisa Novita Sari; Roudhotus Sa’adah; Shandy Santria; Hany Nurpratiwi (Pusat Riset dan Inovasi Nasional, 2023)
Land is a very valuable asset and has a very important role in human life besides that land is also an asset that has a very high selling value over time, so that many people flock to fight over land, triggering conflicts in terms of land. And in this article to find out (1) agrarian conflicts that occur in Indonesia, (2) what obstacles are faced by government agencies in dealing with conflicts (3) how are efforts to resolve conflicts in Indonesia. This research was conducted using a literature study using the Google Schoolar data base with the keywords Agrarian conflict resolution and obtained 8 journals that were used as sources of literature.